Keberlanjutan Penerapan Lubang Resapan Biopori di Kampung Sanitasi Tabiang Banda Gadang - Asmalinda Sy; Iswandi Umar; Nurhasan Syah; Syafrijon (Jurnal Penelitian Pendidikan IPA, 2026)
Household organic waste management represents a critical environmental challenge requiring practical and sustainable solutions, particularly in densely populated urban areas of developing countries. Biopore Infiltration Holes (BIH) constitute an environmentally friendly technology that can be directly implemented at the household level to accelerate organic waste decomposition while simultaneously enhancing soil infiltration capacity. This study aims to conduct a multidimensional sustainability assessment of BIH implementation for household organic waste management in Kampung Sanitasi, Tabiang Banda Gadang Subdistrict. The research employed a descriptive qualitative approach with sustainability analysis using a modified RAPFISH (Rapid Appraisal for Fisheries) method adapted to organic waste management contexts. Data were collected through structured interviews (n=30 households), field observations, questionnaires, and documentation. Each dimension was evaluated based on multiple attributes scored and analyzed using Multi-Dimensional Scaling (MDS) to generate sustainability indices, supported by Monte Carlo simulation and leverage analysis for reliability testing. The multidimensional sustainability analysis revealed varying levels across dimensions: effectiveness (61.69 - moderately sustainable), efficiency (56.91 - moderately sustainable), and practicality (80.52 - highly sustainable), with an overall sustainability score of 66.37 (moderately sustainable). Community participation and environmental literacy emerged as critical determinants of successful implementation. BIH technology demonstrates strong potential as a sustainable household organic waste management strategy, particularly due to its high practicality. The RAPFISH-based multidimensional assessment provides a robust framework for evaluating and improving community-based environmental technologies.